The oral health in Precolombian Peru before - The dental caries in the Precolombian epoch befare - - Borja Villanueva, César Andrés (2005)
There havent been made much investigación work this item our intention in this article is give an approach about the considerations and conclusions of them The pre Columbian Peruvian habitant was afected, gum descases, abrasion, etc. Dental caries affected the litoral habitante more than Andean habitant due to the different geographic regiens show diverse exogenic factors such as climate, diet, uses. As we go through in time and the pre colombian cultures got more development, also caries susceptibility increased. That's why there is a greater number of skulls affected by caries during the inca empire perod.